Aplikasi Pembelajaran Sistem Isyarat Bahasa Indonesia (SIBI) Berbasis Voice Menggunakan OpenSIBI - Fatmawati, Risa; Asmara, Rengga; Prayogi, Yanuar Risah; Hakkun, Rizky Yuniar (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2022)
Sign language is one of the means of communication for people who are deaf and speech impaired, especially between normal people and people with disabilities in the wider community. But in reality, not everyone can understand the meaning and purpose of the sign language used so that there is a lack of knowledge of normal people about sign language in Indonesia and there is still a lack of effective and easy-to-understand digital learning media. In this study, we propose a new approach to create a sign language learning application for normal people using voice as input which can later display the results of visualization of sign language movements in the form of 3D animation. The display of 3D animation movements uses data that refers to the SIBI (Indonesian Language Sign System) curriculum. This Sign Language application was built by utilizing the Google Speech to Text API to process voice input, Java as the programming language used, and MySQL to manage the database. Based on system testing and on users (general public and persons with disabilities) using the SUS (System Usability Scale) method, it can be concluded that the sign language learning application with Android-based voice input is successful in facilitating the sign language learning process and in terms of usability or usability of the application getting an assessment that the application can be accepted by users and is suitable for use as a learning support media because its features can be understood well.